Allele length of the DMPK CTG repeat is a predictor of progressive myotonic dystrophy type 1 phenotypes. (18th March 2019) - Overend, Gayle; Légaré, Cécilia; Mathieu, Jean; Bouchard, Luigi; Gagnon, Cynthia; Monckton, Darren G
Abstract: Myotonic dystrophy type 1 (DM1) is an autosomal dominant inherited disorder caused by expansion of a germline and somatically unstable CTG repeat in the DMPK gene. Previously, CTG repeat length at birth has been correlated to patient age at symptom onset. Attempts to correlate CTG repeat length with progressive DM1 phenotypes, such as muscle power, have proven difficult. To better correlate genotype with progressive phenotypes, we have measured CTG repeat tract length and screened for interrupting variant repeats in 192 study participants from a well-characterized Canadian cohort. We have assessed genotype–phenotype correlations with nine progressive measures of skeletal muscle power and respiratory function. We have built statistical models that include confounding factors such as sex, age, height and weight to further explain variation in muscle power. Our analysis reveals a strong correlation between DM1 genotype and respiratory function and skeletal muscle power, as part of a complex model that includes additional modulators such as sex, age, height, weight and the presence or absence of interrupting variant repeats. Distal skeletal muscle measurements, such as hand pinch and grip strength, show the strongest correlation with disease genotype. Detailed analysis of CTG repeat length, and incorporation of confounding factors, greatly improves the predictive ability of these models. They reveal a greater genetic influence on individual progressive phenotypes than on age at symptom onset and for clinical trials will help optimize stratification and explain patient variability. They will also help practitioners prioritize assessment of the muscular power measurements that correlate best with disease severity.